Lexicalized Unstressed Pronouns Patterns: A Study Based on Corpus Linguistics - Serikaku, Helenice (The ESPecialist, 2015)
Brazilian learners of Spanish as a foreign language frequently have difficulties with unstressed pronouns usage. The difficulty not only concerns using these pronouns with their canonic function of object, but without this function ─ case known as lexicalized unstressed pronouns (PAL). This research aims to identify patterns of PAL as well verbs that co-occur with PAL according to Corpus Linguistics framework and its methodological resources (BERBER SARDINHA, 2000). This paper intended to contribute to a field scarce of studies which is important to pedagogical needs of Brazilian learners of SFL.